The heart and mind in teaching : pedagogical styles through the ages - Lowery, Alyssa Magee; Hayes, William, 1938- (Lanham, Maryland : Rowman & Littlefield, 2014)
"[This book] provides an important historical context for an issue confronting every American teacher, administrator, student, parent, and citizen. As the art of teaching is rapidly replaced by formulas, clinical studies, and one-size-fits-all scientific pedagogy, it is important to ask the question, "How did we get here?" Authors Alyssa Magee Lowery and William Hayes trace the history of teaching from Greek philosophy to twenty-first century educational issues in an effort to provide some perspective in the long art versus science debate, ultimately finding that the two components may be able to coexist peacefully." -- Publisher's description.
Teaching in antiquity -- Teaching methods in early Christianity -- Teaching in the Middle Ages and the European Renaissance -- Teaching in colonial America and the education of the founding fathers -- Teaching in the first public schools -- The progressive education movement -- The normal school and the evolution of teacher education in the United States -- Teaching in the last half of the twentieth century -- The effects of No Child Left Behind on teaching in America -- The impact of the Common Core Curriculum on teaching -- Lesson planning models -- The new emphasis on teacher evaluation -- The impact of educational choice on teaching -- The influence of technology -- The impact of educational research -- Concluding thoughts.
Includes bibliographical references and index.
Keywords: Education -- History; Education -- United States -- History